PENGARUH PENUTUPAN PINTU PERLINTASAN JALAN REL TERHADAP KINERJA LALU LINTAS JALAN RAYA DI PERLINTASAN KALIGAWE SEMARANG DAN KALIWUNGU KENDAL - Mukthy Yusyadiputra; Robby Hermawanto; Bambang Pudjianto; Eko Yulipriyono (Jurnal Karya Teknik Sipil, 2014)
The Intersection between railway crossings with roads have any problems, especially when the railway gate were closed while trains pass. The problem is the queue of vehicles and the time of vehicle back to normal before the crossings opened. Geometric of Kaligawe Road is 4/2D with all types of vehicles and Kaliwungu is 2/2UD dominated by light vehicles. Both are in the class of primary arterial road. The data was collected by surveying directly at the two railway – roadway crossing at peak hours in the morning, afternoon, and evening. The data were taken during the normal flow is the flow rate (flow) vehicle, traffic speed, road geometric, and a long stream of vehicles crossing back to normal when the railway gate is opened. Meanwhile, when the railway gate is closed is the speed of shockwave, railway gate closing time, and a queue of vehicles. The data was then analyzed using the shockwave method, the capacity of the road using Highway Capacity Manual guidelines (MKJI) 1997 and theoretically Greenshields models are then compared the results, in order to obtain the queue length and time of return to normal road traffic due to the effect of the closure of crossings when trains pass. The results of analysis on the existing condition at Kaligawe Semarang and Kaliwungu Kendal still able to accommodate vehicular traffic passing through the intersection, because based on Timetabling 2013 +72 recorded trains pass each day with a headway of trains in peak hour morning, afternoon, and evening the average is 22 minutes if the closure 3-4 minutes. For Kaligawe Road if closure (t) = 3 minutes long queue gained = 0.15 to 0.25 miles with vehicles back to normal after crossing when the door is opened (t2) = 3.913 to 5 minutes, and if t = 4 minutes queue length obtained = 0.2 to 1.66 km with t2 = 5.21 to 6.68 minutes. While on the Road Kaliwungu if t = 3 minutes obtained queue length = 0.078 to 0.366 km with t2 = 4.172 to 11.88 minutes and if t = 4 minutes obtained queue length = 0.105 to 0.5 km with t2 = 5.564 to 15.85 minutes. t2 obtained in Jalan Kaligawe and Kaliwungu still less than 22 and 25 minutes. Responding PT.KAI plan which will operate a double track to increase the frequency of trains ± 72 to ± 200 trains per day. Based on the assumption that the headway of trains is the same every hour it is 7.2 minutes, then the results of the analysis for the Kaligawe road still able to accommodate traffic in the event of the closure 3-4 minutes, but for the Kaliwungu are no longer able to accommodate traffic flow if the closing 3 and 4 minutes because t2 obtained is 11.88 and 15.85 minutes. Besides, the degree of saturation (DS) in Kaligawe road = 0.401 and Kaliwungu = 0,747, to get for good traffic performance, for Kaliwungu Road becomes necessary to change the geometric 4/2D. The results of these observations can be useful in making policy considerations relevant to the response effort DEPARTMENT PT.KAI operate the double track in 2014 in order to maximize the performance of the Road Traffic Road Kaliwungu Kendal and Kaligawe Semarang.